Knowledge and practice about immunization among mothers of under one children delivered at home. - Upadhyaya, Gyanendra (2007)
ABSTRACT: This small scale descriptive study was done in Kathmandu VDC among 50 respondents. The main objective of this research was to find out knowledge and practice about immunization among mothers of under one children delivered at home. In this study majority of the respondents were Tamang i.e 40% (n=20) followed by Brahmin 30% (n=15). Only 28% (n=14) of the respondents were illiterate and 82% (n=41) were agriculture with their occupation. Though cent percent of the respondents had heard about immunization but still 22% (n=10) of the respondents had no idea why the immunization is give to their child. As per immunization schedule, majority of the respondents i.e. 60% (n=30) had knowledge about the age of Measles vaccination followed by BCG 40% (n=20), DPT 26% (n=13), Polio 18% (n=9) respectively. Only 4% (n=2) of the respondents had knowledge about the schedule of Hep-B vaccination. The study showed relatively poor knowledge regarding doses of administration of DPT and Hep.B. Only 14% (n=7) of the respondents knew that DPT is given in three doses and 10% (n=5) knew about the doses of Hep-B vaccine. This study also gives the poor knowledge regarding role of BCG vaccine where only 8% (n=4) gave the correct answer and neither of the respondents knew the role of DPT and Hep.B vaccine. In this study 90% of the respondents had done complete immunization to their child. The study reflects that the mothers need to given awareness about the role of the vaccine and time of dose of administration.